2016
DOI: 10.3892/etm.2016.3366
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-135b has a neuroprotective role via targeting of β-site APP-cleaving enzyme 1

Abstract: Abstract. MicroRNAs (miRs) are a class of endogenous small non-coding RNAs that have been revealed to negatively mediate the expression of their target genes at the post-transcriptional level. Recently, particular miRs have demonstrated an involvement in the pathogenesis of Alzheimer's disease (AD). However, the specific role of miR-135b in AD has yet to be elucidated. The present study aimed to investigate the neuroprotective role of miR-135b, in addition to its underlying mechanism. Herein, reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Other negative regulators of BACE1 also include miR-298/328 (Boissonneault et al, 2009), microRNA-195 (Zhu et al, 2012), miR-135a (Liu et al, 2014), microRNA-135b (Zhang et al, 2016), miR-339-5p (Long et al, 2014), and miR-186 (Kim et al, 2016), all of which negatively correlated with BACE1 expression and exerted regulatory effects by binding the 3’UTR of BACE1.…”
Section: Micrornas Involved In the Aβ Hypothesismentioning
confidence: 99%
“…Other negative regulators of BACE1 also include miR-298/328 (Boissonneault et al, 2009), microRNA-195 (Zhu et al, 2012), miR-135a (Liu et al, 2014), microRNA-135b (Zhang et al, 2016), miR-339-5p (Long et al, 2014), and miR-186 (Kim et al, 2016), all of which negatively correlated with BACE1 expression and exerted regulatory effects by binding the 3’UTR of BACE1.…”
Section: Micrornas Involved In the Aβ Hypothesismentioning
confidence: 99%
“…APP is regulated by miR-16 [25][26][27], miR-101 [28,29], miR-153 [30,31], miR-193b [32], and miR-200b [33]. Similarly, miR-9 [21], miR-15b [34,35], miR-29a/b [21], miR-135a [33], miR-135b [36], miR-195 [37], and miR-339-5p [38] modulate BACE1 expression in different models. Tau is regulated by, among others, miR-16, miR-24c-5p, and miR-132 [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al reported that miR-135b-5p protects osteoblastic cells from dexamethasone-induced apoptosis [ 29 ]. Overexpression of miR-135b-5p has a neuroprotective effect on Alzheimer’s disease by targeting the β-site APP-cleaving enzyme 1 [ 23 ]. miR-135b-5p is decreased in the hippocampus of a rat model of temporal lobe epilepsy and may be involved in the regulation of hippocampal neuron apoptosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-135b-5p has been reported as an anti-apoptotic miRNA [ 21 , 22 ]. A recent study has shown that miR-135b-5p has a neuroprotective effect in Alzheimer’s disease [ 23 ]. However, little is known about the role of miR-135b-5p in regulating neuronal survival during cerebral ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%